Leaf traits and plastic potential of plant species in a light-edaphic gradient from a Restinga in southern Brazil (2016)
Restinga formations grow on sandy spits of coastal plains, an environment whose conditions limit the growth and development of vegetal species. Studies on restinga gradients are good examples of how plants acclimate to restrictive environments. This work compares three woody species co-occurring in four vegetations of a restinga from Southern Brazil. It pinpoints morpho-anatomical attributes that favor the survival of species faced with spatial variability of soil and light conditions. Results indicate that they respond differently to environmental variables on different scales. The plastic response of morphological attributes is more marked than that of anatomical ones. Varronia curassavica and Dodonaea viscosa showed more xeromorphic features on the more stressful restinga formations while Symphyopappus casarettoi varied between xerophyte to mesophyte forms along the gradient. Individual height, fresh and dry leaf masses, leaf area, specific leaf mass and area, leaf density, and water content are particularly noteworthy. These responses are strategies allowing the studied species to survive in restinga environment with highly variable soil nutrient, water availability, and light conditions. The environmental conditions are important features that modulate de plant morphology along the gradient. Keywords: coastal vegetation, leaf morphology, leaf anatomy, light and soil conditions.